PENGARUH STRES DAN KEPUASAN KERJA TERHADAP KEMANGKIRAN (ABSENTEEISM) PEGAWAI DINAS PENDIDIKAN, PEMUDA DAN OLAHRAGA KOTA BUKITTINGGI PROVINSI SUMATERA BARAT - Husnul Alimah Z. Day (Universitas Negeri Jakarta, 2018)
The purpose of this research is to know the effect of stress and job satisfaction toward the Authorities of Education, Youth and Sport of Bukittinggi, West Sumatera Employee’s absenteeism. The research was conducted by using survey method with quantitative approach and path analysis technique. The population of this research is 103 personnel. Research samples selected as much as 82 personnel using simple random sampling technique. The data obtained through questionnaires and analyzed by using path analysis techniques. Based on the results of the data analysis in this research it is concluded: (1) stress has direct positive effect to absenteeism; (2) job satisfaction has direct negative effect to absenteeism; (3) stress has negative effect to job satisfaction